F15. NEGATIVE BELIEF UPDATING BIAS FOR POSITIVE LIFE EVENTS IN PATIENTS WITH SCHIZOPHRENIA. (9th April 2019) - Hu, Huixin; Jiang, Shuyao; Shan, Haidi; Lv, Qinyu; Yi, Zhenghui; Chan, Raymond C K
Abstract: Background: The high levels of low-pleasure beliefs are reported in patients with schizophrenia. However, it is still unclear about the mechanisms of the development and maintenance of these low-pleasure beliefs in this clinical group. In the present study, we aimed to examine how patients with schizophrenia would update their beliefs when receiving information about daily life events, and to explore why patients with schizophrenia would maintain these biased beliefs regarding positive experiences. Methods: Thirty-six out-patients with schizophrenia and thirty demographically matched healthy controls were recruited to complete the belief updating task that was designed to examine the pattern of belief updating. The task included 43 positive and 27 negative daily life events in total. Each trial began with the presentation of a positive/negative life event on the center of screen, and participants were instructed to estimate the probability of experiencing it in the next month. After the first estimation, they were shown the average probability of this event happening to a person in the similar socio-cultural environment and were asked to re-estimate the likelihood of this event. All participants received either good news (the average probability better than expected) or bad news (the average probability worse than expected). Belief update scores were calculated as the difference between the first and the second estimated probabilities, and were used to assess how much the participants incorporated new information into their beliefs. The 2(News: good/bad news) × 2(Group: schizophrenia patients/healthy controls) repeated measures ANOVA was used to analyze the update scores for positive events and negative events separately. The differences in estimation errors, differences in memory, and differences in number of trials were entered as covariates. Results: For positive events, there was a significant main effect of News (F(1, 58) = 4.625, p= 0.036, η2p=0.074) and Group (F(1, 58) = 5.421, p= 0.023, η2p=0.085). The interaction effect between News and Group was marginally significant (F(1, 58) = 2.924, p= 0.093, η2p=0.048). Subsequent analysis revealed that schizophrenia patients showed negative bias in belief updating, specifically, they updated their beliefs to a greater extent in response to bad news than good news, while healthy controls had no bias in updating in response to good and bad news. For negative events, no significant difference was observed in the main effect (News: F(1, 58) = 1.838, p= 0.180, η2p=0.031; Group: F(1, 58) = 0.023 p= 0.881, η2p=0.000) and the interaction effect (F(1, 58) = 0.979, p= 0.327, η2p=0.017). Patients with schizophrenia and healthy controls all updated their beliefs to a greater extent in response to good news than bad news. Discussion: Patients with schizophrenia tended to exhibit negative bias in belief updating only for positive events, but not for negative events. Such a pattern may be crucial for the maintenance of these low pleasure beliefs in these patients. These results highlight the importance of belief updating intervention for patients with schizophrenia.